Dominasi Budaya Patriarki dan Dampak Negatif Fenomena Fatherless pada Masyarakat Gayo - Mentari Mentari (SOSIO DIALEKTIKA, 2024)
The issue of child-rearing in the current era of globalization is highly complex and influenced by various social, cultural, economic, and technological factors. Globalization has also affected family structures, with more families living apart, rising divorce rates, and an increase in single-parent households, contributing to the growing phenomenon of fatherlessness. Indonesia ranks third in the world for the category of fatherlessness. In this situation, not all children can experience the presence of a father. Fatherlessness refers to the absence of a father's role and figure in a child's life, both physically and psychologically. The phenomenon of fatherlessness often arises from parenting paradigms influenced by patriarchal culture. This paper aims to answer the research question of how the dominance of patriarchal culture and the negative impact of the fatherlessness phenomenon affect the Gayo community. This research is qualitative descriptive research, utilizing data collection techniques such as interviews and literature review. The results of this research show that the dominance of patriarchal culture in the Gayo community, influenced by globalization, has a negative impact on children experiencing fatherlessness. This is caused by migration, social conflict, and changes in the kinship system and traditional structures, which strongly place the full responsibility for child-rearing on the mother. The negative impacts on fatherlessness children include mental health issues, low motivation in education, problematic social behaviour, identity crises, and negative effects on the family’s economic situation. There is a need for awareness regarding the presence of fathers in child-rearing and a balanced division of roles between mothers and fathers to achieve gender equality.